Enhanced hot recycled asphalt mixture and process for its preparation

CN122958104APending Publication Date: 2026-10-23ZHONGYIFENG (SUZHOU) MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611301953.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-06-29
Filing Date
2026-08-26
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]为了解决因混合料助剂体系多组分功能独立、协同性差而导致出现再生组分分布不均与纤维界面粘结失效的问题,本申请提供一种增强型热再生沥青混合料及其制备工艺

Benefits of technology

1、由于本申请采用梯度改性玄武岩纤维与废旧沥青铣刨料、新集料、矿粉和基质沥青复配构建再生沥青混合料,附着于玄武岩纤维表面的改性大豆油同时承担老化沥青组分修复与纤维界面粘结改善的双重功能,玄武岩纤维在混合料内部交错搭接形成稳定的空间加筋骨架,获得精简混合料助剂体系、改善再生沥青品质与混合料性能并支撑废旧沥青铣刨料高比例资源化利用的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958104A_ABST
    Figure CN122958104A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of waste asphalt thermal regeneration, and particularly discloses an enhanced thermal regeneration asphalt mixture and a preparation process thereof. The enhanced thermal regeneration asphalt mixture comprises the following raw materials: waste asphalt milling material, new aggregate, mineral powder, gradient modified basalt fiber and matrix asphalt; and the preparation method comprises the following steps: S1, preparing modified soybean oil; S2, mixing cut basalt fiber with ester exchange modified soybean oil to obtain gradient modified basalt fiber; S3, mixing the waste asphalt milling material with the new aggregate through dry mixing to obtain aggregate mixture; S4, adding the gradient modified basalt fiber and superfine mineral powder into the aggregate mixture to obtain dry mixture; S5, adding molten matrix asphalt into the dry mixture for wet mixing to obtain wet mixture; and S6, adding conventional mineral powder into the wet mixture for final mixing and mixing. The asphalt mixture can be used in asphalt pavement major and medium repair regeneration engineering, and has the advantages of simplifying mixture additives and improving the performance of regenerated asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of waste asphalt thermal recycling technology, and more specifically, it relates to an enhanced thermally recycled asphalt mixture and its preparation process. Background Technology

[0002] Hot recycled asphalt mixture technology is a widely used technology for the resource utilization of waste pavement materials in asphalt pavement maintenance engineering in my country. It is applied to major and medium repair projects of asphalt pavement of various grades. This technology involves heating, screening, and mixing waste asphalt milling material, and then compounding it with new aggregates, new asphalt, recycling agents and other raw materials to prepare hot recycled asphalt mixtures. This can realize the recycling of waste asphalt pavement materials, reduce the consumption of virgin materials such as new aggregates and new asphalt, reduce carbon emissions and construction costs of road maintenance projects, and at the same time, through formula optimization, the road performance of hot recycled mixtures can meet the relevant specifications and adapt to the service needs of roads of different traffic levels and different climate regions.

[0003] In related technologies, the functions of asphalt recycling and fiber reinforcement are usually achieved by independent additives. Petroleum-based recyclers can only replenish the light components lost by aged asphalt to complete the asphalt performance repair, but cannot improve the interfacial compatibility between inorganic fibers and organic asphalt. Basalt fiber and other reinforcing materials can only play a structural reinforcement role in the mixture, and have no auxiliary effect on the recycling and repair of aged asphalt. The independent functions of multiple components and poor synergy lead to a complex mixture additive system, which is prone to problems such as uneven distribution of recycled components and failure of fiber interface bonding. At the same time, the high proportion of waste asphalt milling material will significantly reduce the core road performance of recycled mixtures, such as high temperature deformation resistance and low temperature crack resistance, and cannot achieve performance balance under high dosage, thus limiting the resource utilization ratio of waste asphalt milling material. Summary of the Invention

[0004] To address the problem of uneven distribution of recycled components and fiber interface bonding failure caused by the independent functions and poor synergy of multiple components in the mixture additive system, this application provides an enhanced hot recycled asphalt mixture and its preparation process.

[0005] In a first aspect, this application provides an enhanced hot recycled asphalt mixture, employing the following technical solution: This application provides an enhanced hot recycled asphalt mixture, employing the following technical solution: An enhanced hot recycled asphalt mixture comprises the following raw materials in parts by weight: 60-65 parts of waste asphalt milling material, 15-30 parts of new aggregate, 5-8 parts of mineral powder, 0.3-0.5 parts of gradient modified basalt fiber, and 2-4 parts of base asphalt; wherein the gradient modified basalt fiber is obtained by compounding short-cut basalt fiber with modified soybean oil, the mass of the short-cut basalt fiber accounts for 85%-90% of the total mass of the gradient modified basalt fiber, and the mass of soybean oil accounts for 10%-15% of the total mass of the gradient modified basalt fiber.

[0006] By adopting the above technical solution, the modified basalt fiber is used as an integrated reinforcement and modification component; modified soybean oil is used as a common medium for fiber surface modification and asphalt recycling; and a complete mixture system is constructed by combining waste asphalt milling material, new aggregate, mineral powder and matrix asphalt. This allows the modified soybean oil to play a dual role in repairing aged asphalt components and improving fiber interface bonding; while the basalt fiber forms a stable spatial reinforcement skeleton inside the mixture. Therefore, the mixture formulation system is simplified, and the performance of recycled asphalt and the mechanical properties of the mixture are improved simultaneously.

[0007] Preferably, the mineral powder is composed of ultrafine mineral powder and conventional mineral powder; the ultrafine mineral powder accounts for 20% to 30% of the total mass of the mineral powder, and the proportion of particles with a particle size ≤0.075mm in the ultrafine mineral powder is ≥90%; the conventional mineral powder accounts for 70% to 80% of the total mass of the mineral powder.

[0008] By adopting the above technical solution, the mineral powder is separated into two components: ultrafine mineral powder and conventional mineral powder. The ultrafine mineral powder participates in strengthening the fiber surface interface structure and regulating the release rate of recycled components, while the conventional mineral powder undertakes the basic function of filling the aggregate voids. The two work together to improve the gradation and interface properties of the mixture. Therefore, the effects of improving the fiber interface bonding stability, optimizing the release law of recycled components, and ensuring the density of the mixture are achieved.

[0009] Preferably, the high-temperature dynamic stability of the mixture is ≥3800 cycles / mm, the bending failure strain at -10℃ is ≥2850με, and the freeze-thaw splitting strength ratio (TSR) is ≥92%.

[0010] By adopting the above technical solution, the high-temperature deformation resistance, low-temperature crack resistance, and water damage resistance of the mixture are systematically optimized due to the dual effect of gradient modified basalt fiber and the synergistic regulation of graded mineral powder. All road performance characteristics reach the corresponding level. Therefore, the effect of meeting the multi-scenario service requirements of high-content recycled mixture is achieved.

[0011] Preferably, the modified soybean oil is prepared by a mild transesterification reaction of refined soybean oil and anhydrous ethanol, wherein the amount of anhydrous ethanol added is 1% to 2% of the total mass of refined soybean oil.

[0012] By adopting the above technical solution, the refined soybean oil is slightly modified by transesterification with anhydrous ethanol, causing partial alcoholysis of the triglycerides in the soybean oil, generating small molecule fatty acids and monoglyceride components, broadening the chain length distribution range of oil molecules, and increasing the number of polar groups on the molecular surface. Therefore, the interfacial adhesion of soybean oil and the penetration and repair effect of aged asphalt are improved.

[0013] The second aspect is the preparation process of reinforced thermal recycled asphalt mixtures. This application provides a preparation process for reinforced hot recycled asphalt mixtures, employing the following technical solution: A preparation process for reinforced hot recycled asphalt mixtures includes the following steps: S1. Refined soybean oil is mixed with anhydrous ethanol and then subjected to a mild transesterification reaction to obtain modified soybean oil. S2. Short-cut basalt fibers are mixed with the transesterified modified soybean oil and then subjected to medium-temperature thermal oxidation polymerization treatment to obtain gradient modified basalt fibers with a gradient functional oil film formed on the surface. S3. Mix the waste asphalt milled material with the new aggregate and dry mix to obtain a homogeneous and dispersed aggregate mixture; S4. Add the gradient modified basalt fiber and ultrafine mineral powder to the aggregate mixture, and dry mix to obtain a dry mixture with fiber interface anchoring. S5. Add molten matrix asphalt to the dry mixture and wet mix to obtain a wet mixture with uniform asphalt coating. S6. Add conventional mineral powder to the wet mixture for final mixing to obtain reinforced hot recycled asphalt mixture.

[0014] By adopting the above technical solution, the modification effect at each stage is progressively enhanced due to the sequential process of soybean oil transesterification modification, basalt fiber gradient film formation, aggregate dry mixing and homogenization, fiber and ultrafine mineral powder anchoring dry mixing, asphalt coating wet mixing, and conventional mineral powder final mixing. The functional pretreatment of raw materials is completed first, and then interface strengthening, slow release of recycled components and homogenization of the mixture are gradually achieved during the mixing process. The entire process is completed in situ at a conventional mixing plant. Therefore, the preparation effect is achieved with smooth process connection, controllable modification effect and adaptability to existing engineering production conditions.

[0015] Preferably, in step S1, the temperature of the mild transesterification reaction is 80-90°C, and the reaction time with constant temperature stirring is 20-30 min.

[0016] By adopting the above technical solution, the transesterification reaction is controlled within a suitable temperature and time range, allowing soybean oil to undergo only a mild alcoholysis reaction. This generates sufficient polar groups and small molecule components to meet the needs of subsequent fiber interface anchoring and asphalt regeneration. Furthermore, it avoids excessive transesterification, which can lead to excessively small oil molecules, excessive volatilization during subsequent high-temperature mixing, or excessive softening of the asphalt. This ensures that the degree of polymerization and activity of the oil molecules remain within a reasonable range. Therefore, it achieves the effect of regulating the molecular structure of soybean oil while simultaneously considering the dual functions of interface modification and asphalt regeneration.

[0017] Preferably, in step S2, the temperature of the medium-temperature thermal oxidation polymerization treatment is 115~125℃, and the time of the low-speed stirring treatment is 6~8min; the gradient functional oil film includes an interface anchoring inner layer closely attached to the surface of the basalt fiber and a slow-release regeneration outer layer located on the outside, wherein the degree of oil polymerization of the interface anchoring inner layer is higher than that of the slow-release regeneration outer layer.

[0018] By adopting the above technical solution, the basalt fiber and modified soybean oil are subjected to low-speed stirring under medium temperature conditions, which causes the oil to undergo controllable mild thermal oxidative polymerization on the fiber surface. The degree of polymerization of the oil closely attached to the fiber substrate is higher, and it forms a stable adsorption with the fiber surface groups to strengthen the interfacial bonding. The degree of polymerization of the oil on the outer side is lower, and small molecule active components are retained for subsequent repair of aged asphalt. A gradient oil film structure with functional stratification is naturally formed. Therefore, the effect of simultaneously constructing an interfacial anchoring layer and a regenerated slow-release layer on the fiber surface is achieved.

[0019] Preferably, in step S4, the dry mixing time is 15-20 seconds, and the ultrafine mineral powder accounts for 20%-30% of the total mass of the mineral powder. After dry mixing, the ultrafine mineral powder particles are embedded in the interface anchoring inner layer of the gradient functional oil film to form a microscale anchoring structure.

[0020] By adopting the above technical solution, ultrafine mineral powder and gradient modified basalt fiber are simultaneously added to the aggregate mixture for dry mixing; the ultrafine mineral powder particles are embedded in the anchoring oil film layer on the fiber surface under mechanical mixing; a microscale interlocking composite structure is formed to improve the interface's resistance to water loss; at the same time, the ultrafine mineral powder forms a physical barrier on the outside of the oil film; the release rate of recycled components in the subsequent wet mixing stage is adjusted; and excessive softening of local asphalt is avoided; therefore, the effects of strengthening the fiber interface bonding strength and regulating the uniform release of recycled components are achieved.

[0021] Preferably, in step S5, the wet mixing time is 40-45 seconds, and the temperature of the mixture system is maintained at 150-160°C during the mixing process; during the wet mixing process, the slow-release recycled outer layer oil on the outside of the gradient functional oil film is gradually released and diffuses into the aged asphalt of the waste asphalt milling material.

[0022] By adopting the above technical solution, wet mixing of asphalt is carried out within a suitable mixing temperature and time range; the molten matrix asphalt uniformly coats the aggregate and fiber surface; at the same time, the mixing heat drives the low-polymerization degree grease on the outside of the fiber to be gradually released; uniformly diffused and penetrated into the interior of the aged asphalt of the waste asphalt milling material; replenished the lightweight components lost during aging; and ensured the uniform and stable performance of the asphalt mastic; thus, the effect of uniform repair of aged asphalt and balanced performance of the asphalt mastic of the mixture is achieved.

[0023] Preferably, in step S6, the final mixing time is 15-20 seconds, and the temperature of the mixture at discharge is controlled at 150-160℃.

[0024] By adopting the above technical solution, conventional mineral powder is added for final mixing after wet mixing; and the discharge temperature is controlled within a reasonable range; the conventional mineral powder fully fills the voids in the aggregate skeleton; the gradation composition and density of the mixture are optimized; at the same time, the workability of the mixture at the discharge point is guaranteed; and it is adapted to the requirements of subsequent paving and compaction processes; therefore, the overall density and mechanical stability of the mixture are improved, and the quality of subsequent paving construction is guaranteed.

[0025] In summary, this application has the following beneficial effects: 1. Since this application uses gradient modified basalt fiber to compound recycled asphalt mixture with waste asphalt milling material, new aggregate, mineral powder and matrix asphalt, the modified soybean oil attached to the surface of basalt fiber simultaneously undertakes the dual functions of repairing aged asphalt components and improving fiber interface bonding. The basalt fiber interlocks in the mixture to form a stable spatial reinforcement skeleton, thereby achieving the effects of simplifying the mixture additive system, improving the quality of recycled asphalt and the performance of the mixture, and supporting the high-proportion resource utilization of waste asphalt milling material.

[0026] 2. This application preferably uses graded mineral powder components. Because ultrafine mineral powder embeds into the fiber surface oil film during the dry mixing stage, it forms a microscale anchoring structure and regulates the release rate of recycled components. Conventional mineral powder fills the voids in the aggregate skeleton, optimizing the gradation and density of the mixture. This achieves the effects of improving the fiber interface's resistance to water damage, balancing the high-temperature deformation resistance of the mixture with the asphalt recycling effect. 3. In this application, a mild transesterification process is preferred for pretreatment of soybean oil. After mild alcoholysis, the distribution of the molecular chain length of soybean oil is broadened and the number of polar groups is increased, which is suitable for the subsequent fiber interface anchoring and asphalt penetration regeneration requirements, thereby improving the interfacial adhesion of soybean oil and the uniformity of repair of aged asphalt. Attached Figure Description

[0027] Figure 1 This is a flowchart of the preparation process of an enhanced hot recycled asphalt mixture proposed in this application; Figure 2This is a schematic diagram showing the test results of the road performance of the embodiments and comparative examples proposed in this application; Figure 3 This is a schematic diagram showing the test results of the stability performance of the embodiments and comparative examples proposed in this application; Figure 4 This is a schematic diagram showing the test results of the performance of the recycled asphalt binder in the embodiments and comparative examples proposed in this application. Detailed Implementation

[0028] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.

[0029] Technical concept: This application discloses an enhanced hot recycled asphalt mixture and its preparation process. It comprises the following raw materials: waste asphalt milled material, new aggregate, mineral powder, gradient-modified basalt fiber, and base asphalt; the preparation method is as follows: S1, preparing modified soybean oil; S2, mixing short-cut basalt fiber with transesterified modified soybean oil to obtain gradient-modified basalt fiber; S3, dry-mixing waste asphalt milled material with new aggregate to obtain aggregate mixture; S4, adding gradient-modified basalt fiber and ultrafine mineral powder to the aggregate mixture to obtain dry mixture; S5, adding molten base asphalt to the dry mixture for wet mixing to obtain wet mixture; S6, adding conventional mineral powder to the wet mixture for final mixing.

[0030] This application uses gradient-modified basalt fiber to construct recycled asphalt mixtures with waste asphalt milling material, new aggregates, mineral powder, and matrix asphalt. Modified soybean oil adhering to the surface of the basalt fiber simultaneously serves the dual function of repairing aged asphalt components and improving fiber interface adhesion. The basalt fiber interlocks within the mixture to form a stable spatial reinforcing skeleton, achieving the effects of simplifying the mixture additive system, improving the quality and performance of recycled asphalt, and supporting a high proportion of resource utilization of waste asphalt milling material.

[0031] Example 1: This example provides an enhanced hot recycled asphalt mixture, comprising the following raw materials in parts by weight: 60 parts of waste asphalt milling material, 15 parts of new aggregate, 5 parts of mineral powder, 0.3 parts of gradient modified basalt fiber, and 2 parts of base asphalt.

[0032] The mineral powder consists of ultrafine mineral powder and conventional mineral powder, with ultrafine mineral powder accounting for 20% of the total mass of the mineral powder, and particles with a diameter ≤0.075mm accounting for ≥90% of the ultrafine mineral powder. Conventional mineral powder accounts for 80% of the total mass of the mineral powder. The high-temperature dynamic stability of the mixture is ≥3800 cycles / mm, the bending failure strain at -10℃ is ≥2850με, and the freeze-thaw splitting strength ratio (TSR) is ≥92%. The modified soybean oil is obtained by a mild transesterification reaction between refined soybean oil and anhydrous ethanol, with the amount of anhydrous ethanol added being 1% of the total mass of refined soybean oil.

[0033] The above-mentioned method for preparing an enhanced thermally recycled asphalt mixture includes the following steps: S1. Refined soybean oil is mixed with anhydrous ethanol and then subjected to a mild transesterification reaction to obtain modified soybean oil. The temperature for mild transesterification was 80℃, and the reaction time with constant temperature stirring was 20 min.

[0034] S2. Short-cut basalt fibers are mixed with transesterified modified soybean oil and then subjected to medium-temperature thermal oxidation polymerization to obtain gradient modified basalt fibers with a gradient functional oil film on the surface. The temperature of the medium-temperature thermal oxidation polymerization treatment is 115℃, and the time of the low-speed stirring treatment is 6 minutes. The gradient functional oil film includes an interface anchoring inner layer that is closely attached to the surface of the basalt fiber and a slow-release regeneration outer layer located on the outside. The degree of oil polymerization of the interface anchoring inner layer is higher than that of the slow-release regeneration outer layer.

[0035] S3. Mix the waste asphalt milled material with the new aggregate and dry mix to obtain a homogeneous and dispersed aggregate mixture; S4. Add gradient modified basalt fiber and ultrafine mineral powder to the aggregate mixture, and dry mix to obtain a dry mixture with fiber interface anchoring. The dry mixing time is 15 seconds, and the ultrafine mineral powder accounts for 20% of the total mass of the mineral powder. After dry mixing, the ultrafine mineral powder particles are embedded in the interface anchoring inner layer of the gradient functional oil film to form a microscale anchoring structure.

[0036] S5. Add molten base asphalt to the dry mix and wet mix to obtain a wet mix with uniform asphalt coating. The wet mixing time is 40 seconds, and the temperature of the mixture system is maintained at 150℃ during the mixing process. During the wet mixing process, the slow-release recycled outer layer of oil on the outside of the gradient functional oil film is gradually released and diffuses into the aged asphalt of the waste asphalt milling material.

[0037] S6. Add conventional mineral powder to the wet mixture for final mixing to obtain reinforced hot recycled asphalt mixture.

[0038] The final mixing time is 15 seconds, and the temperature of the mixture is controlled at 150℃ when it is discharged.

[0039] Example 2: This example provides an enhanced hot recycled asphalt mixture, comprising the following raw materials in parts by weight: 62.5 parts of waste asphalt milling material, 22.5 parts of new aggregate, 6.5 parts of mineral powder, 0.4 parts of gradient modified basalt fiber, and 3 parts of base asphalt.

[0040] The mineral powder consists of ultrafine mineral powder and conventional mineral powder, with ultrafine mineral powder accounting for 25% of the total mass of the mineral powder, and particles with a diameter ≤0.075mm accounting for ≥90% of the ultrafine mineral powder. Conventional mineral powder accounts for 75% of the total mass of the mineral powder. The high-temperature dynamic stability of the mixture is ≥3800 cycles / mm, the bending failure strain at -10℃ is ≥2850με, and the freeze-thaw splitting strength ratio (TSR) is ≥92%. The modified soybean oil is obtained by a mild transesterification reaction between refined soybean oil and anhydrous ethanol, with the amount of anhydrous ethanol added being 1.5% of the total mass of refined soybean oil.

[0041] The above-mentioned method for preparing an enhanced thermally recycled asphalt mixture includes the following steps: S1. Refined soybean oil is mixed with anhydrous ethanol and then subjected to a mild transesterification reaction to obtain modified soybean oil. The temperature for mild transesterification was 85℃, and the reaction time with constant temperature stirring was 25 min.

[0042] S2. Short-cut basalt fibers are mixed with transesterified modified soybean oil and then subjected to medium-temperature thermal oxidation polymerization to obtain gradient modified basalt fibers with a gradient functional oil film on the surface. The temperature of the medium-temperature thermal oxidation polymerization treatment is 120℃, and the time of the low-speed stirring treatment is 7 minutes. The gradient functional oil film includes an interface anchoring inner layer that is closely attached to the surface of the basalt fiber and a slow-release regeneration outer layer located on the outside. The degree of oil polymerization of the interface anchoring inner layer is higher than that of the slow-release regeneration outer layer.

[0043] S3. Mix the waste asphalt milled material with the new aggregate and dry mix to obtain a homogeneous and dispersed aggregate mixture; S4. Add gradient modified basalt fiber and ultrafine mineral powder to the aggregate mixture, and dry mix to obtain a dry mixture with fiber interface anchoring. The dry mixing time is 17.5s, and the ultrafine mineral powder accounts for 25% of the total mass of the mineral powder. After dry mixing, the ultrafine mineral powder particles are embedded in the interface anchoring inner layer of the gradient functional oil film to form a microscale anchoring structure.

[0044] S5. Add molten base asphalt to the dry mix and wet mix to obtain a wet mix with uniform asphalt coating. The wet mixing time was 42.5 seconds, and the temperature of the mixture system was maintained at 155℃ during the mixing process. During the wet mixing process, the slow-release recycled outer layer of oil on the outside of the gradient functional oil film was gradually released and diffused into the aged asphalt of the waste asphalt milling material.

[0045] S6. Add conventional mineral powder to the wet mixture for final mixing to obtain reinforced hot recycled asphalt mixture.

[0046] The final mixing time is 17.5 seconds, and the temperature of the mixture at the discharge point is controlled at 155℃.

[0047] Example 3: This example provides an enhanced hot recycled asphalt mixture, comprising the following raw materials in parts by weight: 65 parts of waste asphalt milling material, 30 parts of new aggregate, 8 parts of mineral powder, 0.5 parts of gradient modified basalt fiber, and 4 parts of base asphalt.

[0048] The mineral powder consists of ultrafine mineral powder and conventional mineral powder, with ultrafine mineral powder accounting for 30% of the total mass of the mineral powder, and particles with a diameter ≤0.075mm accounting for ≥90% of the ultrafine mineral powder. Conventional mineral powder accounts for 70% of the total mass of the mineral powder. The high-temperature dynamic stability of the mixture is ≥3800 cycles / mm, the bending failure strain at -10℃ is ≥2850με, and the freeze-thaw splitting strength ratio (TSR) is ≥92%. The modified soybean oil is obtained by a mild transesterification reaction between refined soybean oil and anhydrous ethanol, with the amount of anhydrous ethanol added being 2% of the total mass of refined soybean oil.

[0049] The above-mentioned method for preparing an enhanced thermally recycled asphalt mixture includes the following steps: S1. Refined soybean oil is mixed with anhydrous ethanol and then subjected to a mild transesterification reaction to obtain modified soybean oil. The temperature for mild transesterification was 90℃, and the reaction time with constant temperature stirring was 30 min.

[0050] S2. Short-cut basalt fibers are mixed with transesterified modified soybean oil and then subjected to medium-temperature thermal oxidation polymerization to obtain gradient modified basalt fibers with a gradient functional oil film on the surface. The temperature of the medium-temperature thermal oxidation polymerization treatment is 125℃, and the time of the low-speed stirring treatment is 8 minutes. The gradient functional oil film includes an interface anchoring inner layer that is closely attached to the surface of the basalt fiber and a slow-release regeneration outer layer located on the outside. The degree of oil polymerization of the interface anchoring inner layer is higher than that of the slow-release regeneration outer layer.

[0051] S3. Mix the waste asphalt milled material with the new aggregate and dry mix to obtain a homogeneous and dispersed aggregate mixture; S4. Add gradient modified basalt fiber and ultrafine mineral powder to the aggregate mixture, and dry mix to obtain a dry mixture with fiber interface anchoring. The dry mixing time is 20 seconds, and the ultrafine mineral powder accounts for 30% of the total mass of the mineral powder. After dry mixing, the ultrafine mineral powder particles are embedded in the interface anchoring inner layer of the gradient functional oil film to form a microscale anchoring structure.

[0052] S5. Add molten base asphalt to the dry mix and wet mix to obtain a wet mix with uniform asphalt coating. The wet mixing time is 45 seconds, and the temperature of the mixture system is maintained at 160℃ during the mixing process. During the wet mixing process, the slow-release recycled outer layer of oil on the outside of the gradient functional oil film is gradually released and diffuses into the aged asphalt of the waste asphalt milling material.

[0053] S6. Add conventional mineral powder to the wet mixture for final mixing to obtain reinforced hot recycled asphalt mixture.

[0054] The final mixing time is 20 seconds, and the temperature of the mixture is controlled at 160℃ when it is discharged.

[0055] Comparative Example 1: This comparative example refers to the content of Example 1, except that the refined soybean oil is not subjected to light transesterification pretreatment, but is directly subjected to subsequent medium-temperature thermal oxidation polymerization treatment with short-cut basalt fibers. The rest of the content is the same as that of Example 1.

[0056] Comparative Example 2: This comparative example refers to the content of Example 1, except that the S2 step does not perform medium-temperature thermal oxidation polymerization treatment, and the short-cut basalt fibers and modified soybean oil are directly added to the subsequent process after being stirred and mixed at room temperature. The rest of the content is the same as that of Example 1.

[0057] Comparative Example 3: This comparative example refers to the content of Example 1, except that the mineral powder is not separated into ultrafine mineral powder and conventional mineral powder, but all conventional mineral powder is used, and all mineral powder is added uniformly in the final mixing stage of step S6. The rest of the content is the same as Example 1.

[0058] Comparative Example 4: This comparative example refers to the content of Example 1, except that gradient modified basalt fiber is not prepared in advance. The same amount of chopped basalt fiber as in Example 1 is added to the aggregate mixture in step S4 and dry-mixed. The same amount of modified soybean oil as in Example 1 is sprayed into the mixing tank along with the molten matrix asphalt in step S5. The rest of the contents are the same as in Example 1.

[0059] Comparative Example 5: This comparative example refers to the content of Example 1, except that the modified soybean oil is replaced with an equal mass of petroleum-based mineral regenerator, and the modified basalt fiber and subsequent mixture are prepared according to the same process. The rest of the content is the same as Example 1.

[0060] Comparative Example 6: This comparative example refers to the content of Example 1, except that gradient modified basalt fiber is not added, and the modified soybean oil in the same amount as in Example 1 is sprayed into the mixing tank along with the molten matrix asphalt in step S5. The rest of the contents are the same as in Example 1.

[0061] Performance testing Sample preparation: According to the raw material ratios and preparation processes of each embodiment and comparative example, corresponding hot recycled asphalt mixtures were prepared. After the mixtures were mixed, they were molded into standard test specimens of corresponding specifications according to the test requirements of each performance test. All specimens were placed in a curing environment at a standard temperature and left to stand for the specified age. Subsequently, various performance tests were carried out in sequence.

[0062] High-temperature stability performance testing: The cured rutting test specimens are placed in the constant temperature chamber of the rutting tester and kept at the specified test temperature until the internal temperature of the specimen is uniform and stable. The contact pressure and walking speed of the test wheel are adjusted to the set values ​​before starting the test. The deformation of the specimen surface with the number of walking cycles is continuously recorded during the test. The dynamic stability index of the mixture is calculated to characterize the high-temperature resistance to rutting deformation of the mixture. This test is conducted in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" JTGE20-2011.

[0063] Low-temperature crack resistance test: The molded asphalt mixture beam specimens were placed in a low-temperature environment chamber and kept at a sub-zero temperature for a sufficient duration to ensure uniform temperature throughout the specimen. Then, a universal testing machine was used to apply a three-point bending load to the beam specimens at a constant loading rate until fracture occurred. The maximum load and mid-span deflection at failure were recorded. The bending failure strain index of the mixture was calculated to characterize its low-temperature crack resistance. This test was conducted in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" JTGE20-2011.

[0064] Water stability performance testing: The prepared cylindrical splitting tensile test specimens were divided into two groups. The first group of specimens was placed in a dry environment at room temperature as a reference group. The second group of specimens underwent a freeze-thaw cycle treatment consisting of vacuum saturation, low-temperature freezing, and constant-temperature thawing. The splitting tensile strength of both groups of specimens was tested at the specified test temperature. The splitting strength values ​​of the two groups were recorded, and the freeze-thaw splitting strength ratio was calculated to characterize the water stability and resistance to water damage of the mixture. This test was conducted in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" JTGE20-2011.

[0065] Performance testing of recycled asphalt: The Absen extraction method was used to separate and extract the asphalt components from each group of mixture samples. After purification treatment, the recycled asphalt was placed under standard test conditions, and penetration and ductility tests were conducted to determine the penetration and ductility parameters of the recycled asphalt. This was used to evaluate the recycling and repair effect and performance recovery degree of the aged asphalt, and to verify the effect of the recycled components. This test was conducted in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" JTGE20-2011.

[0066] Table 1: Test Results of Road Performance of Hot Recycled Asphalt Mixture

[0067] Table 2: Performance Test Results of Recycled Asphalt Binder

[0068] Example Conclusion: See appendix Figure 1 - Appendix Figure 4 Based on the previous embodiments and comparative examples, the following conclusions can be drawn: Based on Examples 1-3 and Comparative Example 1, and in conjunction with Tables 1 and 2, it can be seen that mild transesterification pretreatment of soybean oil is an important prerequisite for ensuring the modification effect. Transesterification treatment can optimize the molecular structure and polar group distribution of soybean oil, which can not only strengthen the interfacial adsorption between oil and basalt fiber surface and improve the bonding stability of fiber asphalt interface, but also promote the penetration and diffusion of oil into the interior of aged asphalt, improve the repair effect of aged asphalt, and ultimately optimize the multi-dimensional road performance of the mixture.

[0069] Based on Examples 1-3 and Comparative Example 2, and in conjunction with Tables 1 and 2, it can be seen that the gradient functional oil film formed by medium-temperature thermal oxidation polymerization is the core structure for achieving dual effects. The gradient layered oil film structure can construct functional zones on the fiber surface with an inner anchoring layer and an outer slow-release layer. The inner layer strengthens the interface bonding between the fiber and the asphalt, while the outer layer can controllably release recycled components to repair aged asphalt. The absence of this gradient structure will lead to a decrease in interfacial bonding strength and uncontrolled release of recycled components, thereby weakening the overall performance of the mixture.

[0070] Based on Examples 1-3 and Comparative Example 3, and in conjunction with Table 1, it can be seen that the graded mineral powder stepwise feeding process has a significant regulatory effect on the performance of the mixture. The early participation of ultrafine mineral powder in dry mixing can embed into the oil film on the fiber surface to form an anchoring structure, which strengthens the interface's resistance to water damage and regulates the release rate of recycled components, avoiding high-temperature performance degradation caused by recycled oil. The later filling of conventional mineral powder ensures the gradation density of the mixture. The combination of the two can balance the high-temperature stability of the mixture and the asphalt recycling effect.

[0071] Based on Examples 1-3 and Comparative Example 4, and in conjunction with Tables 1 and 2, it can be seen that the pre-preparation of gradient-modified basalt fibers is a key step in achieving dual-function synergy. By pre-loading soybean oil onto the fiber surface and forming a gradient structure, the recycled components can be uniformly dispersed in the mixture system along with the fibers, simultaneously exerting the effects of interface modification and asphalt regeneration. Separate feeding will lead to uneven distribution of recycled components and lack of modification treatment at the fiber interface, thus failing to achieve the optimized effect of dual-effect synergy.

[0072] Based on Examples 1-3 and Comparative Example 5, and in conjunction with Tables 1 and 2, it can be seen that modified soybean oil has a better overall modification effect than petroleum-based regenerators. Soybean oil can not only repair aged asphalt components, but also improve the interfacial compatibility between inorganic fibers and organic asphalt. Petroleum-based regenerators can only play the role of asphalt regeneration and cannot optimize the interfacial bonding performance of fibers. Moreover, they have obvious shortcomings in terms of environmental protection attributes and component synergy.

[0073] Based on Examples 1-3 and Comparative Example 6, and in conjunction with Table 1, it can be seen that there is a significant synergistic effect between the reinforcing effect of basalt fiber and the regeneration effect of soybean oil. The spatial skeleton formed by basalt fiber inside the mixture can offset the risk of high-temperature softening caused by recycled oil and improve the high-temperature deformation resistance of the mixture. Soybean oil improves the toughness of asphalt and optimizes the fiber interface bonding. The combination of the two can simultaneously improve the high-temperature stability and low-temperature crack resistance of the mixture, and solve the performance imbalance problem caused by a single recycled component.

[0074] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A reinforced hot recycled asphalt mixture, characterized in that, The raw materials comprise the following parts by weight: 60-65 parts of waste asphalt milling material, 15-30 parts of new aggregate, 5-8 parts of mineral powder, 0.3-0.5 parts of gradient modified basalt fiber, and 2-4 parts of matrix asphalt; wherein the gradient modified basalt fiber is prepared by compounding chopped basalt fiber with modified soybean oil, wherein the mass of the chopped basalt fiber accounts for 85%-90% of the total mass of the gradient modified basalt fiber, and the mass of the soybean oil accounts for 10%-15% of the total mass of the gradient modified basalt fiber.

2. The reinforced hot recycled asphalt mixture according to claim 1, characterized in that, The mineral powder is composed of ultrafine mineral powder and conventional mineral powder; the ultrafine mineral powder accounts for 20% to 30% of the total mass of the mineral powder, and the proportion of particles with a particle size ≤0.075mm in the ultrafine mineral powder is ≥90%; the conventional mineral powder accounts for 70% to 80% of the total mass of the mineral powder.

3. The reinforced hot recycled asphalt mixture according to claim 1, characterized in that, The mixture has a high-temperature dynamic stability of ≥3800 cycles / mm, a bending failure strain of -10℃ of ≥2850με, and a freeze-thaw splitting strength ratio (TSR) of ≥92%.

4. The reinforced hot recycled asphalt mixture according to claim 1, characterized in that, The modified soybean oil is prepared by a mild transesterification reaction between refined soybean oil and anhydrous ethanol, wherein the amount of anhydrous ethanol added is 1% to 2% of the total mass of refined soybean oil.

5. A process for preparing reinforced thermally recycled asphalt mixture, characterized in that, The method for using an enhanced hot recycled asphalt mixture according to any one of claims 1-4 includes the following steps: S1. Refined soybean oil is mixed with anhydrous ethanol and then subjected to a mild transesterification reaction to obtain modified soybean oil. S2. Short-cut basalt fibers are mixed with the transesterified modified soybean oil and then subjected to medium-temperature thermal oxidation polymerization treatment to obtain gradient modified basalt fibers with a gradient functional oil film formed on the surface. S3. Mix the waste asphalt milled material with the new aggregate and dry mix to obtain a homogeneous and dispersed aggregate mixture; S4. Add the gradient modified basalt fiber and ultrafine mineral powder to the aggregate mixture, and dry mix to obtain a dry mixture with fiber interface anchoring. S5: Add molten base asphalt to the dry mixture and wet mix to obtain a wet mixture with uniform asphalt coating; S6: Add conventional mineral powder to the wet mixture for final mixing to obtain reinforced hot recycled asphalt mixture.

6. The preparation process of an enhanced hot recycled asphalt mixture according to claim 5, characterized in that, In step S1, the temperature of the mild transesterification reaction is 80-90°C, and the reaction time with constant temperature stirring is 20-30 min.

7. The preparation process of an enhanced hot recycled asphalt mixture according to claim 5, characterized in that, In step S2, the temperature of the medium-temperature thermal oxidation polymerization treatment is 115~125℃, and the time of the low-speed stirring treatment is 6~8min; the gradient functional oil film includes an interface anchoring inner layer closely attached to the surface of the basalt fiber and a slow-release regeneration outer layer located on the outside, and the degree of oil polymerization of the interface anchoring inner layer is higher than that of the slow-release regeneration outer layer.

8. The preparation process of an enhanced hot recycled asphalt mixture according to claim 5, characterized in that, In step S4, the dry mixing time is 15-20 seconds, and the ultrafine mineral powder accounts for 20%-30% of the total mass of the mineral powder. After dry mixing, the ultrafine mineral powder particles are embedded in the interface anchoring inner layer of the gradient functional oil film to form a microscale anchoring structure.

9. The preparation process of an enhanced hot recycled asphalt mixture according to claim 5, characterized in that, In step S5, the wet mixing time is 40-45 seconds, and the temperature of the mixture system is maintained at 150-160℃ during the mixing process. During the wet mixing process, the slow-release recycled outer layer of oil on the outside of the gradient functional oil film is gradually released and diffuses into the aged asphalt of the waste asphalt milling material.

10. The preparation process of an enhanced hot recycled asphalt mixture according to claim 5, characterized in that, In step S6, the final mixing time is 15-20 seconds, and the temperature of the mixture is controlled at 150-160℃ when it is discharged.